Pengaruh Kepemilikan Institusional, Non Performing Loan, Loan to Deposit Ratio dan Growth Asset terhadap Kebijakan Dividen pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2015 - Pratiwi, Afrah Dyah (Patria Artha Journal of Accounting dan Financial Reporting, 2017)
This study aims to analyze the influence of institutional ownership, performing loan, loan to deposit ratio and growth asset to dividend policy at banking companies listed on Indonesia stock exchange. The study population is all banking companies listed in Indonesia stock exchange in 2011 – 2015. The sample of the study was determined by purposive sampling method to obtain 7 companies as sample. The method of analysis used is multiple regression analysis. The results of this conclude that the ownership structure has a significant positive effect on dividend policy, non performing loan has a negative effect is not significant to dividend policy, loan to deposit ratio has no significant positive effect on deviden policy. The result of the regression estimation shows the prediction ability of the 4 independent variables to the dividend policy of 23,60% while the remaining 76,40% is influenced by other variables that have not been included in the research.